1969
DOI: 10.1099/00221287-56-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Induction of Chromosome Transfer by Autonomous Sex Factors in Escherichia coli

Abstract: K 12 bacteria, carrying an autonomous F factor or an F-prime factor, enhances the fertility of the population by increasing the number of cells which can transfer the bacterial chromosome. In contrast, under similar conditions the fertility of irradiated Hfr populations falls in proportion to the survivors. Following irradiation, the effect begins to develop after about 30 min. incubation in broth at 37", reaches a peak at about 90 min., and thereafter slowly declines. The effect develops with similar kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

1970
1970
1983
1983

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…The latter authors as well as Cooke & suggested that this factor alternated frequently between integration near the trp region and the autonomous state. Moody & Hayes (1972) also favoured some mode of RI-determined interaction with the bacterial chromosome (see also Evenchik, Stacey & Hayes, 1969) and maintained that the efficient transfer of the trp region could hardly be explained on the basis of spontaneous fragmentation and passive transfer with the sex factor only providing effective contact, as has been suggested for factor ColI (Clowes & Moody, 1966; see also Edwards Clowes, 1972). Participation of P-lacR1drd19 in the process of chromosome transfer was possibly indicated by results given in Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…The latter authors as well as Cooke & suggested that this factor alternated frequently between integration near the trp region and the autonomous state. Moody & Hayes (1972) also favoured some mode of RI-determined interaction with the bacterial chromosome (see also Evenchik, Stacey & Hayes, 1969) and maintained that the efficient transfer of the trp region could hardly be explained on the basis of spontaneous fragmentation and passive transfer with the sex factor only providing effective contact, as has been suggested for factor ColI (Clowes & Moody, 1966; see also Edwards Clowes, 1972). Participation of P-lacR1drd19 in the process of chromosome transfer was possibly indicated by results given in Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome mobilization by F and a number of R plasmids in E. coli can arise by integration of the plasmids into the donor chromosome to form Hfr-type donors (Moody & Runge, 1972) or by some other form of interaction not requiring stable integration (Curtiss & Renshaw, 1969;Evenchik, Stacey & Hayes, 1969;Moody & Hayes, 1972). In Hfr x F-crosses, recombinants are normally F-except when the whole chromosome is transferred.…”
Section: Discussionmentioning
confidence: 99%
“…Media and mating conditions. Nitrate nutrient broth for growing and mating strains and media for propagating bacteriophages have been described previously (16) 10. In crosses with prototrophic donors, rifampin was used for counterselection, whereas selection against auxotrophic donors was done by omission of the required supplement.…”
Section: Methodsmentioning
confidence: 99%